Trumpism and The Global Challenge to Decolonization: Reflections from Southeast Asia - Mohd Ghazi, Ahmad Faris Naiyuddin; Mohammed Yasin, Nazreena; Jaes, Lutfan; Hamzah, Shahidah (Journal of Techno-Social, 2025)
This article explores the global implications of Trumpism as a political and ideological phenomenon and its impact on the ongoing challenges of decolonization, specifically focusing on Southeast Asia. Drawing on qualitative analysis of secondary sources, including political speeches, policy documents, media narratives, and scholarly literature, this study situates Trumpism within a broader resurgence of right-wing populism and neo-imperial rhetoric. While Trumpism is rooted in the American context, its discursive and ideological reach has resonated globally, often reinforcing colonial legacies and obstructing decolonial aspirations in formerly colonized regions. In Southeast Asia, these influences manifest in renewed nationalist movements, anti-globalist rhetoric, and a retreat from critical postcolonial engagement. By examining how Trumpist narratives circulate and take root in Southeast Asian political discourse, this article highlights the complex entanglements between global populism and regional struggles for epistemic and political sovereignty. The study contributes to decolonial scholarship by emphasizing the need for sustained critical reflection on how external political ideologies affect local trajectories of postcolonial development. This study underscores how global populist ideologies can obstruct efforts toward epistemic sovereignty and national self-determination in postcolonial societies.